Effects of Selected Secondary Metabolites in Leaf Extract of Jatropha Tanjorensis on Some Gonadal Hormones in Male Wistar Rats - John, Akighir; Bawa, Inalegwu; John, Anyam; Eje Yakubu, Ojochenemi; Ikani Richard, Odama (Journal of Biotechnology and Biomedical Science, 2020)
Background and Objective The use of medicinal plants in industrialized societies for extraction and development of many drugs and other chemotherapeutics and traditionally for herbal remedies has increased in recent times. Plant–based medicine is essential in health care services with about 80% global population relying on it because of its cheap source and availability. Jatropha tanjorensis is one such plant used by males and females of childbearing age for treatment of reproductive problems such as infertility. Literature on isolation and characterization of the secondary metabolites in this plant may not be common. Against this backdrop, this research work was carried out to isolate, characterize and determine the effects of J. tanjorensis on the gonadal hormones of male wistar rats. Materials and Methods The secondary metabolites were isolated, characterized, and identified using nuclear magnetic resonance. The experiment was conducted using 25 male wistar rats weighing between 180-200 g randomized into 5 groups, 3 controls and 2 treatment groups of 5 rats each. The treatment groups received 25 mg/kg body weight of phytol and lupeol orally by gastric lavage for 14 days. The animals were anaesthetized and blood samples collected for hormonal assay. Result The experimental data was analyzed using one-way analysis of variance (ANOVA) with Statistical Package for Social Sciences (SPSS) version 17.0, while the post hoc test assessed using Duncan Multiple Range Test at p ≥ 0.05. There was a significant decrease (p ˂ 0.05) in the levels of FSH, LH and TST in the treatment groups when compared to the control groups. The motility and sperm count decrease significantly (p ˂ 0.05) when treatment groups were compared to the control animals. The secondary metabolites, phytol and lupeol present in the leaf extract of Jatropha tanjorensis were responsible for the decrease in some of the gonadal hormones studied.
Keywords: Characterization; gonadal hormones; isolation; Jatropha tanjorensis; Secondary metabolites; rat.